Study on the Air Dispersion Characteristics along the West Coast of Korean Peninsula - Pokhrel, Rajib; Cho, Inhyeong; Sharma, Ram K; Lee, Heekwan (Journal of the Institute of Engineering, 2012)
When the temperature difference between land and sea surface along coastline is large enough, thermally induced circulation is likely developed in the coastal region, called as Sea/Land (S/L) breeze. It has been an important issue in coastal region because of its significant role for the transport, dispersion of air pollutants generated in coastal regions. Meso-scale modeling was carried out using the commercial modeling tool ‘A2C flow / A2C t&d (A2C represents the Atmospheric to Computational fluid dynamics and t&d represents the transport and diffusion)’ to characterize the meso-scale circulation of pure breeze in the study region (125.22E, 36.32N to 127.95E, 38.39N) in late July for typical summer conditions of Korea. Maximum potential temperature differences were approximately 5K and 14K in early morning and mid day, respectively in the study domain. Strong land breeze was observed around 6AM and it was neutralized to transition stage between 9AM ~ 10AM then the sea breeze started. Maximum speed of sea breeze, approximately 2.5m/s was found around 3PM which is about double of land breeze (1.5m/s). With the declination of sun energy with the passing of time, sea breeze lost its momentum and reached to transition stage between (9PM ~ 10PM). The penetration lengths of sea breeze and land breeze are approximately 25km~30km and 20km~25km, respectively while the suction lengths of sea breeze and land breeze are approximately 15km~20km each. In addition, the maximum depths of the S/L breeze are approximately 400m and 1200m, respectively in early morning and sometimes in mid day along the coastal area. DOI: http://dx.doi.org/10.3126/jie.v8i3.5936 JIE 2011; 8(3): 94-104